ANALISA SUSEPTIBILITAS MAGNETIK DAN KANDUNGAN LOGAM BERAT AKIBAT POLUTAN KENDARAAN BERMOTOR DI BEBERAPA RUAS JALAN KOTA PEKANBARU - Vischa Vahyra; Salomo Salomo (Komunikasi Fisika Indonesia, 2020)
The research on the magnetic susceptibility, mass susceptibility, and heavy metal content due to automotive contaminants using magnetic susceptibility and X-ray fluorescence  has been performed. Samples were taken on three roads in Pekanbaru City, i.e. Jendral Sudirman, Ahmad Yani and Pangeran Hidayat Road. The sample was dried, sifted, separated between magnetic and non-magnetic particles, identified and analyzed. The magnetic induction value of the concentrate as a function of current (200,400,600,800,1000) mA was determined using the Pasco PS-2162 magnetic probe and 2500 winding solenoid. The magnetic induction value also increased when the electrical current was increased.  The findings of this analysis showed that concentrates had the magnetic susceptibility values (4888.8–11095.8) × 10-5, while the mass susceptibility of concentrates had values (2284.48–7513.05) × 10-8 m3/kg.  The XRF test is done on three concentrates, which are JS 08, AY 01, and PH 13. The XRF test results showed that all the concentrates contained Mn, Ni, Cu, Zn and Pb heavy metals. Based on the threshold value of heavy metals as soil contaminants, it was established that the content of Cu, Zn, and Pb at JS 08, AY 01, and PH13 concentrations exceeded the threshold. Ni material had reached the threshold only to focus on JS 08.